2016
DOI: 10.1007/s13361-016-1338-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Covalent Bond Formation in Gas-Phase Peptide–Peptide Ion Complexes with the Photoleucine Stapler

Abstract: Abstract. Noncovalent complexes of hydrophobic peptides GLLLG and GLLLK with photoleucine (L*) tagged peptides G(L* n L m )K (n = 1,3, m = 2,0) were generated as singly charged ions in the gas phase and probed by photodissociation at 355 nm. Carbene intermediates produced by photodissociative loss of N 2 from the L* diazirine rings underwent insertion into X−H bonds of the target peptide moiety, forming covalent adducts with yields reaching 30%. Gas-phase sequencing of the covalent adducts revealed preferred b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
51
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…The gas-phase chemistry of photoleucine and photomethionine-containing peptide ions has been studied with the aim to understand their properties [3,4] and exploit their photochemistry for peptide-ligand footprinting in gas-phase ion-molecule complexes [5,6]. Collisioninduced dissociation under slow heating conditions of singly and doubly charged L*-and M*-tagged peptide ions proceeds by competing loss of N 2 and backbone dissociations [3].…”
mentioning
confidence: 99%
“…The gas-phase chemistry of photoleucine and photomethionine-containing peptide ions has been studied with the aim to understand their properties [3,4] and exploit their photochemistry for peptide-ligand footprinting in gas-phase ion-molecule complexes [5,6]. Collisioninduced dissociation under slow heating conditions of singly and doubly charged L*-and M*-tagged peptide ions proceeds by competing loss of N 2 and backbone dissociations [3].…”
mentioning
confidence: 99%
“…Cross‐linking using L*‐tagged and M*‐tagged peptides in solution is known to achieve only low yields of identifiable products . In contrast, UV photodissociation of mass‐selected ion‐molecule complexes (UVPD‐MS 2 ) and the ensuing intramolecular bond insertion reactions have been reported to proceed with up to 30–40% yields of covalent products that can be further analyzed by tandem mass spectrometry after ion mass separation and collisional excitation in an ion trap (CID‐MS 3 ) …”
Section: Methodsmentioning
confidence: 99%
“…Previous research of gas‐phase cross‐linking in peptide–peptide ion complexes used synthetic peptides that were photolabeled with L* in specific sequence positions . Sequence analysis of the cross‐linked peptides, combined with Born–Oppenheimer molecular dynamics, indicated that the non‐covalent interactions in the complexes were chiefly due to hydrogen bonding of charged and polar groups whereas the nonpolar L* side chains were not involved.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations